First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Effects of N-acetylcysteine treatment on frontal glutamate and GABA levels and associations with drinking quantity in people with co-occurring posttraumatic stress disorder and alcohol use disorder - James J. Prisciandaro; Amber M. Jarnecke; Jane E. Joseph; Kevin M. Gray; Elizabeth J. Santa Ana; Sudie E. Back (Psychopharmacology, 2025)
Rationale Though half of people with posttraumatic stress disorder (PTSD) develop alcohol use disorder (AUD), co-occurring PTSD and AUD (PTSD + AUD) is associated with more severe clinical outcomes relative to either alone and little remains known about the pathophysiology of PTSD + AUD. PTSD and AUD have each been associated with marked dysfunction in brain glutamate and GABA systems, making these systems promising targets for pharmacological intervention, including N-acetylcysteine (NAC), which restores extracellular glutamate concentrations via GLT-1 and System Xc-. Objectives and Methods Based on promising results from our pilot study of NAC, we recently completed a 12-week, randomized, double-blind, placebo-controlled clinical trial of NAC for PTSD + AUD. As part of this trial, we acquired proton MR spectroscopy ( 1 H-MRS) data at pretreatment and ~ 8-weeks posttreatment in a subsample of ( n = 44) participants to evaluate whether NAC significantly affects frontal glutamate levels (i.e., represented by Glx, glutamate + glutamine), with exploratory evaluation of GABA and glutathione levels, and whether NAC-related changes in neurometabolite levels correspond to decreased drinking and/or PTSD symptoms, in people with PTSD + AUD. Results We found that NAC was associated with significantly higher frontal Glx ( t = 2.45, p = 0.017), and significantly lower GABA ( t = -2.82, p = 0.007) but equivalent glutathione ( t = -1.00, p = 0.321), levels relative to placebo. Finally, lower NAC-related GABA, but not Glx or glutathione, levels were significantly associated with decreased drinks per drinking day ( t = 2.57, p = 0.014), but not percent drinking days or PTSD symptoms ( p s > 0.10). Conclusions Though preliminary, these findings are consistent with the mechanistic hypothesis that NAC reduces drinking quantity through its effects on excitatory and inhibitory neurotransmission in people with PTSD + AUD.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Differential gene expression in the equine endometrium and conceptus from Day 11 to 16 post-ovulation - Alysa JL Giudici; Michael J Byron; Leah N Ramsaran; Lara S Chong; Jennine Lection; Bradley C Back; Megan E Bernard; Soon Hon Cheong; Mariana Diel de Amorim (Journal of Equine Veterinary Science, 2023)

Diazotrophy modulates cyanobacteria stoichiometry through functional traits that determine bloom magnitude and toxin production - Nicole D. Wagner; Felicia S. Osburn; Raegyn B. Taylor; Jeffrey A. Back; C. Kevin Chambliss; Bryan W. Brooks; J. Thad Scott (Limnology and Oceanography, 2023)
Harmful cyanobacterial blooms are an increasing threat to water quality. The interactions between two ecophysiological functional traits of cyanobacteria, diazotrophy (nitrogen [N]‐fixation) and N‐rich cyanotoxin synthesis, have never been examined in a stoichiometric explicit manner. We explored how a gradient of resource N : phosphorus (P) affects the biomass, N, P stoichiometry, light‐harvesting pigments, and cylindrospermopsin production in a N‐fixing cyanobacterium, Aphanizomenon . Low N : P Aphanizomenon cultures produced the same biomass as populations grown in high N : P cultures. The biomass accumulation determined by carbon, indicated low N : P Aphanizomenon cultures did not have a N‐fixation growth trade‐off, in contrast to some other diazotrophs that maintain stoichiometric N homeostasis at the expense of growth. However, N‐fixing Aphanizomenon populations produced less particulate cylindrospermopsin and had undetectable dissolved cylindrospermopsin compared to non‐N‐fixing populations. The pattern of low to high cyanotoxin cell quotas across an N : P gradient in the diazotrophic cylindrospermopsin producer is similar to the cyanotoxin cell quota response in nondiazotrophic cyanobacteria. We suggest that diazotrophic cyanobacteria may be characterized into two broad functional groups, the N‐storage‐strategists and the growth‐strategists, which use N‐fixation differently and may determine patterns of bloom magnitude and toxin production in nature.

Neogene-Quaternary evolution of the La Baja Guajira basin, Colombia: Burial and thermal history with implications on petroleum systems - Leidy Castro-Vera; Ralf Littke; Stefan Back; Rocío Bernal-Olaya; Martin Reyes; J. Alejandro Mora-Bohórquez; A. Johamna Romero (Journal of South American Earth Sciences, 2023)

Incorporating parameter variability into Monod models of nutrient‐limited growth of non‐diazotrophic and diazotrophic cyanobacteria - Jingyu Wang; Scott C. James; Jeffery A. Back; J. Thad Scott (Environmental Microbiology, 2022)
Models are widely used tools in aquatic science to understand the mechanism of phytoplankton growth and anticipate the occurrence of harmful algal blooms. However, model parameterization remains challenging and issues that may introduce prediction uncertainty exist. Many models use the Monod equation to predict cyanobacteria growth rate based on ambient nutrient concentrations. The half‐saturation concentrations in the Monod equation varies greatly among different studies and depends on environmental conditions. In this study, we estimated the growth rate due to nutrient limitations for two cyanobacteria species ( Microcystis aeruginosa and Dolichospermum flos‐aquae ) using a modified Monod model which allows the half‐saturation concentration to vary according to initial nitrogen (N) conditions. The model is calibrated against observations from laboratory experiment where cyanobacteria growth and ambient nutrient concentrations were measured simultaneously, which is rarely done in the literature. Our results show this modified model produce better predictions on growth rate and biomass, indicating many commonly used mechanistic models may need improvement regarding phytoplankton growth representation. Furthermore, our study quantifies the flexibility in cyanobacteria growth parameter across a wide range of environmental N in eutrophic lakes thus provides important information for large‐scale modelling applications.

The crystal structure and redefinition of utahite - Owen P. Missen; Stuart J. Mills; Michael S. Rumsey; Malcolm E. Back; Veronica E. Di Cecco; William D. Birch; John Spratt (Mineralogy and Petrology, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Radiation, inflammation and the immune response in cancer - Kelly J. McKelvey; Amanda L. Hudson; Michael Back; Tom Eade; Connie I. Diakos (Mammalian Genome, 2018)

Frequency of Candida spp. in the Oral Cavity of Brazilian HIV-Positive Patients and Correlation with CD4 Cell Counts and Viral Load - G. N. Back-Brito; A. J. Mota; T. C. Vasconcellos; S. M. R. Querido; A. O. C. Jorge; A. S. M. Reis; I. Balducci; Cristiane Yumi Koga-Ito (Mycopathologia, 2009)

Influence of a selectable marker gene hpt on agronomic performance in transgenic rice - K-M. Kim; D. E. Lee; H. Song; Y. I. Kuk; S. Jung; J. O. Guh; P. S. Baenziger; K. Back (Cereal Research Communications, 2004)

Lack of FasL-mediated killing leads to in vivo tumor promotion in mouse Lewis lung cancer - J.-K. Lee; T. J. Sayers; T. C. Back; J. M. Wigginton; R. H. Wiltrout (Apoptosis, 2003)

Growth and carbon stock change in eucalypt woodlands in northeast Australia: ecological and greenhouse sink implications - W. H. Burrows; B. K. Henry; P. V. Back; M. B. Hoffmann; L. J. Tait; E. R. Anderson; N. Menke; T. Danaher; J. O. Carter; G. M . McKeon (Global Change Biology, 2002)
Data from 57 permanent monitoring sites are used to document the growth in woody vegetation and estimate the carbon sink in 27 M ha of eucalypt woodlands (savannas), contained within c. 60 M ha of grazed woodlands in Queensland (northeast Australia). The study sites are shown to be representative of the environment and structure of the eucalypt woodlands in the defined study area. Mean basal area increment for all live woody plants in 30 long‐term sites, with an average initial basal area of 11.86 ± 1.38 (SE) m 2 ha −1 , was 1.06 m 2 ha −1 over a mean 14 years timeframe. The majority of the measurement period, commencing between 1982 and 1988, was characterized by below‐average rainfall. The increase in live tree basal area was due primarily to growth of existing trees (3.12 m 2 ha −1 ) rather than establishment of new plants (0.25 m 2 ha −1 ) and was partly offset by death (2.31 m 2 ha −1 ). A simple but robust relationship between stand basal area and stand biomass of all woody species was developed for the eucalypt dominant woodlands. Analysis of above‐ground carbon stocks in live and standing dead woody plants gave a mean net above‐ground annual carbon increment for all 57 sites of 0.53 t C ha −1 y −1 , similar to values estimated elsewhere in world savannas. Published root : shoot ratios were used to infer C flux in woody root systems on these sites. This results in an estimated sink in above‐ and below‐ground biomass of 18 Mt C y −1 over the eucalypt woodlands studied, and potentially up to 35 Mt C y −1 if extended to all grazed woodlands in Queensland. It is suggested that introduction of livestock grazing and altered fire regimes have triggered the change in tree‐grass dominance in these woodlands. Thus, change in carbon stocks in the grazed woodlands of Queensland is identified as an important component of human‐induced greenhouse gas flux in Australia, equivalent in magnitude to c . 25% of the most recently published (1999) total estimated national net emissions. The latter inventory takes into account emissions from land clearing, but does not include the sink identified in the present study. This sequestration also represents a small but significant contribution to the global terrestrial carbon sink.

Subcellular localization of hepatitis C viral proteins in mammalian cells - J.-E. Kim; W. K. Song; K. M. Chung; S. H. Back; S. K. Jang (Archives of Virology, 1999)

Chirp (2–7 kHz) echo characters in the Ulleung Basin - S. K. Chough; S. H. Lee; J. W. Kim; S. C. Park; D. G. Yoo; H. S. Han; S. H. Yoon; S. B. Oh; Y. B. Kim; G. G. Back (Geosciences Journal, 1997)

Constraints on establishment of plains cottonwood in an urban riparian preserve - Gregor T. Auble; Michael L. Scott; Jonathan M. Friedman; Jennifer Back; Victor J. Lee (Wetlands, 1997)

Comparison and fine mapping of both high and low neutralizing monoclonal antibodies against the principal neutralization domain of HIV-1 - J. P. M. Langedijk; Nicole K. T. Back; Elaine Kinney-Thomas; Claudine Bruck; Myriam Francotte; J. Goudsmit; R. H. Meloen (Archives of Virology, 1992)